Separator for secondary battery, secondary battery including the same, and method for manufacturing the secondary battery
The secondary battery separation membrane, featuring a PVDF-HFP coating layer with optimized lamellar thickness and using a high-boiling-point solvent, addresses the challenges of maintaining inorganic particles and preventing electrolyte dissolution, thereby improving battery stability and safety.
Patent Information
- Application Number
- JP2024556705
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-10-31
- Filing Date
- 2023-11-01
- Publication Date
- 2025-04-16
AI Technical Summary
Existing secondary battery separation membranes face challenges in maintaining inorganic particles at high temperatures and preventing excessive dissolution in the electrolyte, which can lead to safety issues and reduced battery stability.
A secondary battery separation membrane is developed, comprising a porous substrate with a coating layer made of polyvinylidene fluoride-co-hexafluoropropylene copolymer (PVDF-HFP) and inorganic particles. The lamellar thickness of the PVDF-HFP is optimized to 2.5 to 3.2 nm, and a polar organic solvent with a boiling point of 120°C or higher is used to enhance the binder's stability and adhesion.
The optimized membrane effectively prevents the dissociation of inorganic particles and maintains the stability of the secondary battery, even at high temperatures, thereby enhancing the mechanical durability, heat resistance, and overall safety of the battery.
Smart Images

Figure 2025511609000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a separator for a secondary battery, and more particularly to a separator for a secondary battery, a secondary battery including the same, a method for manufacturing the separator, and a method for manufacturing the secondary battery. [Background technology]
[0002] Lithium-ion batteries, a representative example of secondary batteries, are basically composed of a positive electrode, a separator, a negative electrode, and an electrolyte. They are representative of high-energy-density energy devices that can be charged and discharged while reversibly converting chemical energy and electrical energy, and are widely used in small electronic devices such as mobile phones and laptops. In recent years, their application to hybrid electric vehicles (HEVs), plug-in EVs, electric bicycles (E-bikes), and energy storage systems (ESSs) has been rapidly expanding in response to environmental issues, high crude oil prices, and energy efficiency and storage. Lithium-ion batteries are stable electrochemical elements insulated by a separator, but internal or external abnormal battery phenomena or impacts can cause a short circuit between the positive and negative electrodes, which can lead to heat generation and explosion, so ensuring the thermal and chemical safety of the separator as an insulator is of utmost importance.
[0003] One of the major research topics in secondary batteries is to improve safety at high temperatures. For example, secondary batteries may explode due to high temperatures and high pressures inside the battery that may be caused by abnormal operating conditions of the battery, such as internal short circuits, overcharging exceeding the allowable current and voltage, exposure to high temperatures, and deformation due to dropping or external impact. In reality, internal short circuits caused by contraction or damage of the separator when the battery is exposed to high temperatures are very serious, and much research has been conducted on the cause and countermeasures for this. When storing secondary battery cells, there is a risk of fire due to the possibility of internal short circuits caused by the contraction of the separator, but excessive coating to prevent this may cause problems such as insufficient capacity of the battery cell, increased resistance of the battery cell, and increased thickness of the battery cell. Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present invention is to provide a separator for a secondary battery that can effectively retain inorganic particles even at high temperatures after injection of an electrolyte, thereby improving the safety of the secondary battery.
[0005] Another object of the present invention is to provide a separator for a secondary battery that can effectively prevent a binder from being excessively dissolved in an electrolyte due to a swelling phenomenon caused by the binder absorbing the electrolyte.
[0006] Another object of the present invention is to provide a secondary battery including the separator for secondary batteries.
[0007] Another object of the present invention is to provide a method for producing a secondary battery that can ensure the stability of the secondary battery.
[0008] The object of the present invention is not limited to the object mentioned above, and other objects and advantages of the present invention not mentioned can be understood from the following description and will be more clearly understood by the embodiment of the present invention. In addition, it is easily understood that the object and advantages of the present invention can be realized by the means and combinations thereof shown in the claims. [Means for solving the problem]
[0009] To achieve the above object, a first embodiment of the present invention provides a separator for a secondary battery, comprising a porous substrate and a coating layer disposed on at least one surface of the porous substrate, the coating layer comprising polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) and inorganic particles, and a lamellar thickness of the polyvinylidene fluoride-hexafluoropropylene copolymer in the coating layer is 2.5 to 3.2 nm.
[0010] In a second embodiment of the present invention for achieving the above object, the porous substrate in the first embodiment may include at least one selected from the group consisting of polyolefin, polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfide, and polyethylene naphthalene.
[0011] In a third embodiment of the present invention to achieve the above object, the inorganic particles in the first or second embodiment may be inorganic particles having a dielectric constant of 5 or more, inorganic particles having lithium ion transport ability, or a mixture thereof.
[0012] In the fourth embodiment of the present invention for achieving the above object, in any one of the first to third embodiments, the inorganic particles are Al2O3, SiO2, ZrO2, AlO(OH), Al(OH)3, Mg(OH)2, BaSO4, TiO2, BaTiO3, Pb(Zr x Ti 1-x )O3 (PZT, where 0 < x < 1), Pb 1-x La x Zr 1-y Ti y O3 (PLZT, where 0 < x < 1, 0 < y < 1).), (1 - x)Pb(Mg 1 / 3 Nb 2 / 3 )O 3-x PbTiO3 (PMN - PT, where 0 < x < 1), HfO2, SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, SiC, lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y - based glass (0 < x < 4, 0 < y < 13), lithium lanthanum titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3), lithium germanium thiophosphate (Li x Ge y P z S w , 0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), lithium nitride (Li x N y , 0 < x < 4, 0 < y < 2), SiS2 - based glass (Li x Si y S z , 0 < x < 3, 0 < y < 2, 0 < z < 4), P2S5 - based glass (Li x P y S zIt may also be selected from the group consisting of (0 < x < 3, 0 < y < 3, 0 < z < 7) and mixtures of two or more of these.
[0013] In the fifth embodiment of the present invention for achieving the above object, in any one of the first to fourth embodiments, the content of the monomer derived from hexafluoropropylene in the polyvinylidene fluoride - hexafluoropropylene copolymer may be 8 to 15% by weight.
[0014] In the sixth embodiment of the present invention for achieving the above object, in any one of the first to fifth embodiments, the weight average molecular weight (Mw) of the polyvinylidene fluoride - hexafluoropropylene copolymer may be 300,000 to 600,000 g / mol.
[0015] In the seventh embodiment of the present invention for achieving the above object, in any one of the first to sixth embodiments, the air permeability of the separator for secondary batteries may be 160 sec / 100 cc or less.
[0016] In another embodiment of the present invention for achieving the above object, a method for manufacturing a separator for secondary batteries can be provided.
[0017] In the eighth embodiment of the present invention for achieving the above object, there is provided a method for manufacturing a separator for secondary batteries, including (S1) a step of coating a composition for forming a coating layer on at least one surface of a porous substrate, and (S2) a step of drying the composition for forming a coating layer to form a coating layer, wherein the composition for forming a coating layer includes a polyvinylidene fluoride - hexafluoropropylene copolymer, inorganic particles, and a solvent, and the solvent includes a polar organic solvent having a boiling point of 120°C or higher.
[0018] In a ninth embodiment of the present invention to achieve the above object, in the eighth embodiment, the composition for forming a coating layer in step (S2) may be dried at 100 to 170° C. for 0.5 to 1.5 hours.
[0019] In order to achieve the above object, in a tenth embodiment of the present invention, in the eighth or ninth embodiment, the polar organic solvent may be selected from the group consisting of 4-dimethylaminopyridine, 1-pentanol, ethylene glycol, dimethylsulfoxide, dimethylformamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, and a mixture of two or more thereof.
[0020] In an eleventh embodiment of the present invention for achieving the above object, in any one of the eighth to tenth embodiments, the content of the solvent may be 20 to 40 wt % based on the total weight of the composition for forming a coating layer.
[0021] In order to achieve the above object, a twelfth embodiment of the present invention provides a separator for a secondary battery manufactured by the manufacturing method according to any one of the eighth to eleventh embodiments.
[0022] In order to achieve the above object, in a thirteenth embodiment of the present invention, there is provided a secondary battery including: a negative electrode; a positive electrode; a separator interposed between the negative electrode and the positive electrode, preferably the separator described in any one of the first to seventh or twelfth embodiments; and an electrolyte solution.
[0023] In order to achieve the above object, in a fourteenth embodiment of the present invention, there is provided a method for manufacturing a secondary battery, the method including: (S1) manufacturing an electrode assembly by sequentially stacking a positive electrode, a separator described in any one of the first to seventh or twelfth embodiments, and a negative electrode; (S2) inserting the electrode assembly into a battery case, and then injecting an electrolyte into the battery case; and (S3) storing the battery case with the electrolyte injected therein at 55 to 65°C. Effect of the Invention
[0024] According to one aspect of the present invention, the lamellar thickness of the binder in the coating layer can be increased to an appropriate level. As a result, the lamellar thickness increased to an appropriate level can effectively prevent an increase in dissociation caused by swelling of the binder by the electrolyte. As a result, the binder with low solubility in the electrolyte can well hold the inorganic particles contained in the coating layer, effectively improving the stability of the secondary battery.
[0025] In addition to the above-mentioned effects, specific effects of the present invention will be described together with the following explanation of specific contents for carrying out the invention. [Brief description of the drawings]
[0026] [Figure 1] 1 is a vertical cross-sectional view of a separator for a secondary battery according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a graph showing the change in lamellar thickness of the binder (PVDF-HFP) in the separation membranes according to Examples 1 to 3 and Comparative Examples 1 to 3 when the solvent contained in the composition for forming a coating layer was changed. [Diagram 3] FIG. 13 is a diagram showing the solubility of a binder in an electrolyte solution depending on the type of solvent when the temperature is changed. [Figure 4a] 1 shows the results of wet adhesion evaluation of a coating layer to a porous substrate in a separation membrane of Comparative Example 1. [Figure 4b] 1 shows the results of wet adhesion evaluation of a coating layer to a porous substrate in a separation membrane of Example 3. [Figure 4c] 1 shows the results of wet adhesion evaluation of a coating layer to a porous substrate in a separation membrane of Comparative Example 2. [Figure 4d] 1 shows the results of wet adhesion evaluation of a coating layer to a porous substrate in a separation membrane of Example 1. [Diagram 5] 5A is a scanning electron microscope (SEM) photograph of a cross section of a secondary battery including a separator according to Comparative Example 1 (FIG. 5A), and FIG. 5B is a SEM photograph of a cross section of a separator according to Example 1 (FIG. 5B). [Figure 6] 2 is a cross-sectional SEM (scanning electron microscope) photograph of secondary batteries including the separators according to Comparative Example 1 and Example 1. [Figure 7] 1 is a graph showing the capacity retention rate according to the number of cycles (3 cycles) of secondary batteries including the separators according to Comparative Example 1 and Example 1. FIG. [Figure 8] 1 shows the results of comparing secondary battery cells including the separators according to Comparative Example 1 and Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] Hereinafter, each component of the present invention will be described in more detail so that a person having ordinary skill in the art to which the present invention pertains can easily implement the present invention. However, this is merely an example, and the scope of the present invention is not limited to the following content.
[0028] Unless otherwise limited, the detailed description defining or embodying the relevant components is applicable to all inventions and is not limited to the description of a particular invention, i.e., the present disclosure may refer to a combination of embodiments even if they are disclosed individually.
[0029] Additionally, the singular forms include the plural forms throughout the detailed description and the appended claims unless expressly stated otherwise.
[0030] As used herein, the terms "having" or "comprising" specify the presence of referenced elements but do not exclude the presence or addition of one or more other elements, unless the context clearly indicates otherwise. However, unless otherwise clearly indicated, "having" or "comprising" and the like include "consisting essentially of" and "consisting of."
[0031] As used herein, the term "essentially comprises" has the meaning "comprises at least 70%", preferably "comprises at least 80%", and most preferably "comprises at least 90%". When referring to the amounts of components of a mixture of substances, the % is by weight relative to the total weight of each mixture. For example, a material that essentially comprises polyethylene comprises polyethylene in an amount of 70% by weight or more based on the total weight of the material.
[0032] Additionally, the terms "about" and "substantially" as used herein are used to mean within the tolerances of manufacturing and materials inherent in the circumstances specified, and precise or absolute numerical values may be referenced to prevent unscrupulous infringers from unjustly predating and to aid in the understanding of the contents of the disclosure.
[0033] Throughout the specification, "A and / or B" means one or both of A and B.
[0034] Polymer chains may crystallize in the form of lamellae (plate-like bodies). The lateral dimensions may generally range from 1 to 25 μm. In such plates, the polymer chains may be arranged approximately perpendicular to the upper and lower surfaces. In this specification, "lamellar thickness" is defined to mean the total height of the platelet model crystal morphology when the polymer chains have a curved shape to form a platelet crystal morphology.
[0035] One embodiment of the present invention relates to a separator for a secondary battery, the separator comprising a porous substrate and a coating layer disposed on at least one surface of the porous substrate, the coating layer comprising polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) and inorganic particles, and the lamellar thickness of the polyvinylidene fluoride-hexafluoropropylene in the coating layer may be 2.5 to 3.2 nm.
[0036] In the preparation of a separator, when acetone is used as a solvent for dispersing the binder contained in a conventional composition for forming a coating layer, i.e., a composition including a binder, inorganic particles, and acetone as a solvent, a problem occurs in that the binder dissolves in the electrolyte and precipitates, causing the inorganic particles to peel off. As a result, the content of inorganic particles in the coating layer decreases, resulting in a decrease in mechanical durability, heat resistance, and stability of the secondary battery. According to an embodiment of the present invention, a polar organic solvent having a boiling point of at least 120°C, such as a cyclic amide (solvent) having a relatively lower solubility in PVDF-HFP than acetone, is used as a solvent contained in the composition for forming a coating layer, thereby making it possible to increase the lamellar thickness of the binder in the coating layer to an appropriate level. As a result, the increased lamellar thickness can effectively prevent an increase in the degree of dissociation due to the swelling phenomenon of the binder caused by the electrolyte. As a result, the binder with a low solubility in the electrolyte can well hold the inorganic particles contained in the coating layer, effectively improving the mechanical durability, heat resistance, and stability of the secondary battery.
[0037] The configuration of the present invention will be described in more detail below with reference to FIG.
[0038] 1. Separator for secondary battery and its manufacturing method
[0039] FIG. 1 is a vertical cross-sectional view of a separator for a secondary battery according to an embodiment of the present invention.
[0040] Referring to FIG. 1, a separator for a secondary battery (100) according to the present invention includes a porous substrate (10) and a coating layer (20).
[0041] (Porous base material)
[0042] The porous substrate (10) according to the present invention can provide a path for lithium ion migration while electrically insulating the negative electrode and positive electrode to prevent short circuits, and can be a porous structure having high resistance to the electrolyte and fine pore diameters.
[0043] The material of the porous substrate (10) may be any organic or inorganic material having electrical insulation, without any particular limitation. The porous substrate (10) may comprise, essentially comprise, or consist of, for example, one or more selected from the group consisting of polyolefin, polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfide, and polyethylene naphthalene. Specifically, the porous substrate (10) may comprise, essentially comprise, or consist of a polyolefin or a mixture of two or more different polyolefins. Preferably, the porous substrate may comprise or consist of polyethylene. Polyolefins such as polyethylene have excellent coating properties, and can reduce the thickness of the separator, thereby increasing the proportion of the electrode active material layer in the battery and increasing the capacity per volume. Specifically, the weight average molecular weight (Mw) of the polyolefin may be 100,000 to 500,000 g / mol. If the weight average molecular weight of the polyolefin is less than the above range, it may be difficult to secure sufficient mechanical properties, and if it exceeds the above range, the shutdown function may not be realized or molding may be difficult. The shutdown function refers to the effect of blocking the movement of ions and preventing thermal runaway of the battery by dissolving the thermoplastic resin and blocking the pores of the porous substrate when the temperature of the secondary battery becomes high.
[0044] The thickness of the porous substrate (10) may be, for example, 3 to 12 μm or 5 to 12 μm, about 9 μm. If the thickness of the porous substrate is less than the numerical range, the conductive barrier function may be insufficient, and if it exceeds the numerical range, the resistance of the separation membrane may increase excessively. The thickness of the porous substrate (or other thicknesses such as the thickness of the coating layer) can be measured using a thickness measuring instrument such as the Mitutoyo VL-50S, particularly according to the following steps: - Press and hold button 2, make sure that the measuring tip touches the floor and display 4 turns green, - When the display turns green, press button 3 to set the zero point (make sure that the number in the window turns to 0), - Press button 1 to return the tip to its original position, - Place the punched-out membrane test piece on the surface plate with a size of 5 cm x 5 cm, - Press and hold button 2 to check the thickness of the separation membrane (a total of 5 points can be measured and recorded: top / bottom / left / right / center).
[0045] The porous substrate may have a porosity of 10-90%, 20-80%, 30-70%, 40-50%, or about 45%. The term "porosity" as used herein means the ratio of voids in a structure to the total volume, expressed in vol%, and may be mixed with void fraction, degree of porosity, etc. Porosity may be measured by any method known in the art for such purpose. In particular, the porosity of the porous substrate, as well as the porosity of other materials, may be measured using a commonly used Hg porosimeter, for example, a mercury porosimeter (AUTOPORE V, manufactured by Micromeritics).
[0046] The average diameter of the pores in the porous substrate (10) may be, for example, 10 to 100 nm. The pores in the porous substrate have an interconnected structure, allowing gas or liquid to pass from one side of the porous substrate to the other side. The average diameter of the pores in the porous substrate (or any other diameter of the pores mentioned herein) can be calculated from the pore size distribution measured using a capillary flow porometer (CFP-1500-AE) method. The relationship between air pressure and flow rate can be measured using a porometer for a dry porous substrate (dry sample) and a wet porous substrate (wet sample), respectively, and the size and distribution of the pores can be confirmed through the ventilation curve (dry curve) of the dry sample and the ventilation curve (wet curve) of the wet sample. The method is a method in which the porous substrate is moistened with a wetting solution having a low surface tension, and then pressurized with a gas to push out the wetting solution that fills the pores of the porous substrate. To measure pore size, for example, the porous substrate to be measured is moistened with a wetting solution (Galwick solution), and then the air pressure on one side of the porous substrate is gradually increased. If the air pressure applied is greater than the capillary attraction of the wetting solution present in the pores, the wetting solution blocking the pores is pushed out, and the size and distribution of the pores can be measured based on the pressure and flow rate at the moment of pushing out.
[0047] (Coating layer)
[0048] The coating layer 20 according to the present invention can improve the mechanical strength and heat resistance of the separator for the secondary battery, and can increase the ion conductivity within the secondary battery.
[0049] The coating layer (20) according to the present invention can be disposed on at least one surface of the porous substrate (10). Specifically, the coating layer (20) can be disposed on one surface of the porous substrate (10), or on both surfaces of the porous substrate (10).
[0050] The porosity of the coating layer (20) may be 30 to 80%, specifically 40 to 70% or 40 to 50%. The term "porosity" as used herein means the ratio of voids in a structure to the total volume, is expressed in vol%, and may be used interchangeably with porosity, degree of porosity, etc. In the present invention, the porosity of the coating layer may be measured using, for example, a commonly used Hg porosimeter, for example, a mercury porosimeter (AUTOPORE V manufactured by Micromeritics).
[0051] When the porosity of the coating layer is within the above range, the permeability of lithium ions may be favorable, and the surface opening rate is not too high, so that the adhesive strength between the separator and the electrode can be maintained at an appropriate level.
[0052] The average size of the pores in the coating layer (20) may be 20 to 1,000 nm, specifically 100 to 500 nm. Here, the pore size refers to the diameter of the pore, which is the longest distance between two opposing outer surfaces of the pore. When the average size of the pores in the coating layer satisfies the above numerical range, the pores may not be blocked due to the expansion of the binder resin in the coating layer, and the function as an insulating film may be well maintained, so that the self-discharge characteristics after the secondary battery is manufactured may be maintained at an appropriate level. The average size of the pores in the coating layer may be calculated through SEM (scanning electron microscope) image analysis.
[0053] The coating layer (20) according to the present invention is a dried composition for forming a coating layer, and can be obtained by coating a porous substrate with the composition for forming a coating layer and then drying the composition. Specifically, the composition for forming a coating layer includes polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP), inorganic particles, and a solvent. During the production of the coating layer, the solvent may evaporate.
[0054] The polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) can provide a binding force between the porous substrate and the coating layer as a binder, and can promote the formation of a surface or point bonding structure between a plurality of inorganic particles contained in the coating layer, thereby fixing the inorganic particles in the coating layer so that they do not fall off.
[0055] The content of the hexafluoropropylene monomer derived from hexafluoropropylene in the polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP) may be 5 to 20% by weight, specifically 6 to 18% by weight, and more specifically 8 to 15% by weight. The content of the HFP monomer in PVDF-HFP is 1 H-NMR and / or 19 The content of the HFP monomer in the PVDF-HFP may be determined by F-NMR. If the content of the HFP monomer in the PVDF-HFP is less than the above range, it may dissolve in the electrolyte, resulting in a decrease in stability, and if it exceeds the above range, it may result in a problem of a soft cell being manufactured because wet adhesion is not formed. For example, the content of the hexafluoropropylene monomer (HFP) may be defined as the weight percent of the repeating unit consisting of the molecular structure (-CF2CF(CF3)-) derived from hexafluoropropylene in the following [Chemical Formula 1] (where m+n=100 weight%).
[0056] [ka]
[0057] According to another embodiment of the present invention, the content of the polyvinylidene fluoride-hexafluoropropylene copolymer may be 7 to 18 wt%, specifically 7 to 13 wt%, and more specifically 7 to 11 wt%, based on the total weight of the composition for forming the coating layer. The coating layer may be formed by drying the composition, particularly by removing volatile components of the composition. The content of PVDF-HFP after drying may be 12 to 24 wt%, specifically 15 to 21 wt%, more specifically 17 to 19 wt%, for example, about 18 wt%, based on the total weight of the coating layer. When the content of the polyvinylidene fluoride-hexafluoropropylene copolymer is within the above numerical range, the adhesive strength between the electrode and the separator for the secondary battery is maintained at an appropriate level, and at the same time, the detachment of inorganic particles can be effectively prevented.
[0058] According to another embodiment of the present invention, the weight average molecular weight (Mw) of the polyvinylidene fluoride-hexafluoropropylene copolymer may be 300,000 to 600,000 g / mol, specifically, 350,000 to 500,000 g / mol. When the weight average molecular weight of the polyvinylidene fluoride-hexafluoropropylene copolymer is within the above numerical range, the coating property of the composition for forming a coating layer can be appropriately maintained, and the inorganic particles can be effectively prevented from being detached from the coating layer. The weight average molecular weight of the polyvinylidene fluoride-hexafluoropropylene copolymer can be measured, for example, by gel permeation chromatography (GPC: PL GPC220, Agilent Technologies). Specifically, TCB (trichlorobenzene) was used as the solvent, and measurements were performed using an Agilent Efficient High Thermal RI FID detector with an injection volume of 200 μL (corrected with a cubic function, standard: polystyrene) under conditions of a column temperature of 160°C, a sample concentration of 1.0 mg / mL, and a flow rate of 1.0 mL / min.
[0059] The inorganic particles 21 according to the present invention can contribute to improving the mechanical strength and heat resistance of the separator membrane for secondary batteries. Specifically, the inorganic particles are not particularly limited as long as they are electrochemically stable. That is, the inorganic particles that can be used in the present invention are those in which oxidation and / or reduction reactions do not occur within the operating voltage range of the secondary battery to which they are applied (for example, 0 to 5 V based on Li / Li + ). If there is no such reaction, they are not particularly limited.
[0060] As an example, when using inorganic particles with a high dielectric constant as the inorganic particles, it can contribute to an increase in the dissociation degree of electrolyte salts in the liquid electrolyte, such as lithium salts, and improve the ionic conductivity of the electrolyte solution. For the reasons described above, the inorganic particles can be inorganic particles with a dielectric constant of 5 or more, inorganic particles having lithium ion transfer ability, or a mixture thereof.
[0061] The inorganic particles with a dielectric constant of 5 or more are one or more mixtures selected from the group consisting of Al2O3, SiO2, ZrO2, AlO(OH), Al(OH)3, Mg(OH)2, BaSO4, TiO2, BaTiO3, Pb(Zr x Ti 1-x )O3 (PZT, where 0 < x < 1), Pb 1-x La x Zr 1-y Ti y O3 (PLZT, where 0 < x < 1, 0 < y < 1), (1 - x)Pb(Mg 1 / 3 Nb 2 / 3 )O 3-x PbTiO3 (PMN - PT, where 0 < x < 1), HfO2, SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, and SiC.
[0062] The inorganic particles having lithium ion transfer ability are lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate (Li x Al y Ti z(PO4)3, where 0 < x < 2, 0 < y < 1, 0 < z < 3, (LiAlTiP) x O y glass system (0 < x < 4, 0 < y < 13), lithium lanthanum titanate (Li x La y TiO3, where 0 < x < 2, 0 < y < 3), lithium germanium thiophosphate (Li x Ge y P z S w , where 0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), lithium nitride (Li x N y , where 0 < x < 4, 0 < y < 2), SiS2 - based glass (Li x Si y S z , where 0 < x < 3, 0 < y < 2, 0 < z < 4), and P2S5 - based glass (Li x P y S z , where 0 < x < 3, 0 < y < 3, 0 < z < 7), and can be one or more mixtures selected from the group consisting of them.
[0063] For example, the average particle size (D50) of the inorganic particles can be 1 nm to 10 μm for forming a coating layer with a uniform thickness and an appropriate porosity. Specifically, it can be 10 nm to 2 μm, more specifically 50 nm to 1 μm, 50 - 200 nm, or 100 nm. The "average particle size (D50)" means the particle size at the 50% point of the cumulative distribution of the number of particles according to the particle size. The average particle size can be measured using the laser diffraction method. Specifically, after dispersing the powder to be measured in a dispersion medium, it is introduced into a commercially available laser diffraction particle size measuring device (for example, Microtrac S3500). When the particles pass through the laser beam, the difference in the diffraction pattern according to the particle size is measured to calculate the particle size distribution.
[0064] A separator according to one aspect of the present invention, i.e., a separator including a coating layer of PVDF-HFP having a lamellar thickness of 2.5 to 3.2 nm, can be produced by a method for producing a separator for a secondary battery, comprising the steps of (S1) coating at least one surface of a porous substrate (10) with a composition for forming a coating layer; and (S2) drying the composition for forming a coating layer to form a coating layer (20). The composition for forming a coating layer includes polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), inorganic particles, and a solvent, and the solvent includes a polar organic solvent having a boiling point of 120° C. or higher.
[0065] The solvent according to the present invention, i.e., the solvent of the composition for forming a coating layer used in producing the coating layer (20), can function to adjust the lamellar thickness of the binder (PVDF-HFP) 22 in the coating layer (20), and at the same time, can ensure that the binder 22 and the inorganic particles 21 in the composition for forming a coating layer are uniformly dispersed.
[0066] According to the present disclosure, the solvent may be a polar organic solvent with a boiling point of 120° C. or higher. According to the present disclosure, a solvent may be considered a polar solvent if its polarity is 5 or higher according to Snyder (Snyder, Modern Methods of Pharmaceutical Analysis, Second Edition, Volume 2, Roger E. Schirmer, CRC Press, 1990).
[0067] The polar organic solvent can have a boiling point of at least 130° C., at least 140° C., at least 150° C., at least 160° C., at least 170° C., at least 180° C., at least 190° C., or at least 200° C. The polar organic solvent can have a boiling point of 300° C. or less, 290° C. or less, 280° C. or less, 270° C. or less, 260° C. or less, 250° C. or less, 240° C. or less, 230° C. or less, 220° C. or less, or 215° C. or less.
[0068] In one embodiment, the polar organic solvent may be selected from the group consisting of 4-dimethylaminopyridine (DMAP), 1-pentanol, ethylene glycol, dimethylsulfoxide (DMSO), dimethylformamide (DMF), N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), and a mixture of two or more thereof.
[0069] The polar organic solvent having a boiling point of 120° C. or more according to the present invention may include or consist of a cyclic amide or a mixture of two or more of these. Specifically, it may include or consist of any one selected from the group consisting of N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP) and mixtures thereof. Generally, in the art, the role of a solvent contained in a composition for forming a coating layer is limited because the composition for forming a coating layer is dried after being used to uniformly disperse the binder and inorganic particles in the composition for forming a coating layer. According to one embodiment of the present invention, the lamellar thickness of the binder in the coating layer can be increased to an appropriate level by using a cyclic amide (solvent) having a high boiling point and high polarity or a solubility in PVDF-HFP relatively lower than acetone as the solvent contained in the composition for forming a coating layer. As a result, the lamellar thickness is increased to an appropriate level, which effectively prevents an increase in dissociation caused by swelling of the binder due to the electrolyte, and the binder, which has a low solubility in the electrolyte, can effectively hold the inorganic particles contained in the coating layer, thereby effectively improving the stability of the secondary battery.
[0070] According to another embodiment of the present invention, the content of the solvent in the composition for forming a coating layer may be 20 to 70 wt%, specifically 20 to 50 wt%, more specifically 20 to 40 wt%, based on the total weight of the composition for forming a coating layer. When the content of the solvent is within the above range, the lamellar thickness of the binder in the coating layer may be increased, and the increased lamellar thickness can effectively prevent an increase in the degree of dissociation caused by the swelling phenomenon of the binder due to the electrolyte. As a result, the binder with a low solubility in the electrolyte can well hold the inorganic particles contained in the coating layer, effectively improving the stability of the secondary battery.
[0071] The composition for forming a coating layer according to one aspect of the present invention may be dried by a step of drying at 100 to 170° C. for 0.5 to 1.5 hours, specifically, at 100 to 150° C. for 0.8 to 1.2 hours, and more specifically, at 100 to less than 120° C. for 0.8 to 1.0 hour, or at 100 to 115° C. for 0.8 to 1.0 hour. In this case, the composition for forming a coating layer according to the aspect may be on a laboratory scale.
[0072] The step of drying the composition for forming a coating layer according to another aspect of the present invention may be at 120 to 170°C for 3 minutes or less, 130 to 150°C for 2 minutes or less, or 130 to 140°C for 1 minute or less, or 130°C. In this case, the composition for forming a coating layer according to the aspect may be mass-produced. When the drying temperature and drying time of the composition for forming a coating layer are within the above numerical ranges, the lamellar thickness of the polyvinylidene fluoride-hexafluoropropylene copolymer (binder) in the coating layer may be adjusted to an appropriate level.
[0073] That is, taking into account both the laboratory scale and the mass production scale, the composition for forming a coating layer may be dried at 100 to 170° C. for 0.5 to 1.5 hours; or at about 130° C. for 3 minutes or less.
[0074] In the coating layer (20) according to the present invention, the lamellar thickness of the polyvinylidene fluoride-hexafluoropropylene copolymer 22 may be 2.5 to 3.2 nm, specifically 2.5 to 3.0 nm, more specifically 2.6 to 2.9 nm. For example, the lamellar thickness of the polyvinylidene fluoride-hexafluoropropylene copolymer in the coating layer may be analyzed by a shadowing method using an electron microscope or a method using a small angle x-ray scattering (SAXS) device. The polyvinylidene fluoride-hexafluoropropylene copolymer (binder) may form a platelet crystal form in the coating layer by drying a polar organic solvent such as a cyclic amide (solvent) in the coating layer forming composition. In the coating layer, the lamellar thickness of the polyvinylidene fluoride-hexafluoropropylene copolymer may vary depending on the type and content of the binder in the composition for forming the coating layer, the type and content of the solvent, and the drying temperature and drying time of the solvent. According to an embodiment of the present invention, by deriving an optimal combination of the type and content of the binder, the type and content of the solvent, and the drying temperature and drying time of the solvent, it is possible to provide a separator for a secondary battery having an optimal lamellar thickness that contributes to the stability of the secondary battery.
[0075] According to another embodiment of the present invention, the air permeability of the separator for secondary batteries may be 180 sec / 100 cc or less, specifically 160 sec / 100 cc or less, more specifically 158 sec / 100 cc or less, more specifically 150 to 158 sec / 100 cc. The air permeability of the separator for secondary batteries is the time it takes for 100 cc of air at a certain pressure to pass through a unit area of the separator, and may vary independently depending on the type and content of the solvent, the drying temperature and drying time of the solvent, the thickness of the separator, and the porosity of the separator. The shorter the time it takes for 100 cc of air to pass through the separator, the better the air permeability performance, and thus the rate characteristics of the battery can be improved. For example, the air permeability of the separator for secondary batteries can be measured using an air permeability meter commercially available in the art.
[0076] 2. Secondary battery
[0077] Another embodiment of the present invention may provide a secondary battery including a negative electrode, a positive electrode, a separator interposed between the negative electrode and the positive electrode, and an electrolyte. Descriptions that overlap with those described above will be briefly described or omitted.
[0078] (Negative electrode)
[0079] The negative electrode according to the present invention may include a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode active material layer may include a negative electrode active material, a conductive material, and a negative electrode binder.
[0080] The negative electrode current collector can play a role of transmitting electrons from the outside so that an electrochemical reaction occurs with the negative electrode active material, or receiving electrons from the negative electrode active material and sending them to the outside. For example, as the negative electrode current collector, copper, stainless steel, aluminum, nickel, titanium, fired carbon, or those obtained by surface treatment with carbon, nickel, titanium, silver, etc. on the surface of aluminum or stainless steel can be used. Specifically, transition metals that adsorb carbon well, such as copper and nickel, can also be used as the current collector. For example, the thickness of the negative electrode current collector can be 6 μm to 20 μm, but the thickness of the negative electrode current collector is not limited thereto.
[0081] The negative electrode active material can play a role of storing or releasing lithium ions and generating electricity. For example, as the negative electrode active material, at least one of silicon-based active material particles and graphite-based active material particles can be included.
[0082] The silicon-based active material particles can be one or more selected from the group consisting of Si, SiOx (0 < x ≤ 2), Si-C composites, and Si-Y alloys (Y is any one element selected from the group consisting of alkali metals, alkaline earth metals, transition metals, group 13 elements, group 14 elements, and rare earth elements).
[0083] The graphite-based active material particles can include one or more selected from the group consisting of artificial graphite, natural graphite, graphitized carbon fibers, and graphitized mesocarbon microbeads.
[0084] The content of the negative electrode active material can be 80 to 97% by weight based on the total solid content contained in the negative electrode active material layer.
[0085] The conductive material can improve the conductivity between active material particles in the electrode or with a metal current collector, and prevent the binder from acting as a non-conductor. The conductive material can be, for example, one or a mixture of two or more conductive materials selected from the group consisting of graphite, carbon black, carbon fiber, metal fiber, metal powder, conductive whisker, conductive metal oxide, activated carbon, and polyphenylene derivatives, and more specifically, one or a mixture of two or more conductive materials selected from the group consisting of natural graphite, artificial graphite, super-p, acetylene black, ketjen black, channel black, furnace black, lamp black, summer black, denka black, aluminum powder, nickel powder, zinc oxide, potassium titanate, and titanium oxide.
[0086] The negative electrode binder can suppress separation between the negative electrode active material particles or between the negative electrode and the current collector. As the negative electrode binder, a polymer commonly used in electrodes in the art can be used. Examples of such negative electrode binders include, but are not limited to, poly(vinylidene fluoride co-hexafluoropropylene), poly(vinylidene fluoride-co-trichloroethylene), poly(methylmethacrylate), poly(ethylhexylacrylate), poly(butylacrylate), poly(acrylonitrile), poly(vinylpyrrolidone), poly(vinyl acetate), poly(ethylene-co-vinyl acetate), poly(ethylene oxide), polyacrylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, and the like. Examples of the cellulose acetate propionate include, but are not limited to, cyano ethyl pullulan, cyano ethyl poly(vinylalcohol), cyanoethylcellulose, cyano ethylsucrose, pullulan, and carboxyl methyl cellulose.
[0087] (positive electrode)
[0088] The positive electrode according to the present invention may include a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. The positive electrode active material layer may include a positive electrode active material, a conductive material, and a positive electrode binder.
[0089] For example, the positive electrode current collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery. Specifically, the positive electrode current collector can be made of copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like, or an aluminum-cadmium alloy. The positive electrode current collector can usually have a thickness of 6 to 20 μm.
[0090] For example, the positive electrode active material may include a lithium transition metal oxide. The lithium transition metal oxide may be, for example, Li x1 CoO2(0.5 <x1<1.3)、Li x2 NiO2(0.5 <x2<1.3)、Li x3 MnO2(0.5 <x3<1.3)、Li x4 Mn2O4(0.5 <x4<1.3)、Li x5 (Ni a1 Co b1 Mn c1 )O2(0.5 <x5<1.3、0<a1<1、0<b1<1、0<c1<1、a1+b1+c1=1)、Li x6 Ni 1-y1 Co y1 O2(0.5 <x6<1.3、0<y1<1)、Li x7 Co 1-y2 Mn y2 O2(0.5 <x7<1.3、0≦y2<1)、Li x8 Ni 1-y3 Mn y3 O2(0.5 <x8<1.3、O≦y3<1)、Li x9 (Ni a2 Co b2 Mn c2 )O4(0.5 <x9<1.3、0<a2<2、0<b2<2、0<c2<2、a2+b2+c2=2)、Li x10 Mn2-z1 Ni z1 O4 (0.5 < x10 < 1.3, 0 < z1 < 2), Li x11 Mn 2-z2 Co z2 O4 (0.5 < x11 < 1.3, 0 < z2 < 2), Li x12 CoPO4 (0.5 < x12 < 1.3), and Li x13 It may be one or more selected from the group consisting of FePO4 (0.5 < x13 < 1.3).
[0091] The conductive material used for the positive electrode may be the same as or different from the conductive material used for the negative electrode.
[0092] The positive electrode binder may be the same as or different from the negative electrode binder.
[0093] (Electrolyte solution)
[0094] The electrolyte solution according to the present invention can contain a solvent and a lithium salt.
[0095] The solvent according to the present invention may be, for example, one or a mixture of two or more selected from the group consisting of propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), gamma-butyrolactone (GBL), fluoroethylene carbonate (FEC), methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, propyl acetate, pentyl acetate, methyl propionate, ethyl propionate, ethyl propionate and butyl propionate.
[0096] The lithium salt according to the present invention is, for example, NO 3- , F - , Cl - , Br - , I -, PF6 - The anions may include, for example,
[0097] The secondary battery according to the present invention may be a cylindrical, square, or pouch-type secondary battery, but is not particularly limited as long as it corresponds to a charge / discharge device.
[0098] Another embodiment of the present invention provides a battery module including the secondary battery as a unit cell, and a battery pack including the battery module. The battery pack can be used as a power source for one or more medium- to large-sized devices selected from the group consisting of power tools, electric vehicles (EVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs), and power storage systems.
[0099] 3. Manufacturing method of secondary battery
[0100] Another embodiment of the present invention may provide a secondary battery, particularly a method for manufacturing the above-mentioned secondary battery, including: (S1) a step of manufacturing an electrode assembly by sequentially stacking a positive electrode, the separator, specifically, a separator including a coating layer including PVDF-HFP having a lamellar thickness of 2.5 to 3.2 nm, and a negative electrode; (S2) a step of inserting the electrode assembly into a battery case and then injecting an electrolyte into the battery case; and (S3) a step of storing the battery case with the electrolyte injected therein at 40 to 80° C. Specifically, the step (S3) may be a step of storing the battery case with the electrolyte injected therein at 50 to 70° C., or 55 to 65° C.
[0101] When the battery case into which the electrolyte is injected in step (S3) is stored within the above temperature range, if the lamella thickness range of the binder according to the present invention satisfies the appropriate range, the binder will not dissolve in the electrolyte and the wet adhesive strength may be increased. As a result, the stiffness of the cell is increased, the cell transfer process may proceed efficiently, and the stability of the cell may be ensured. If the lamella thickness range of the binder is outside the appropriate range or if a lamellar structure cannot be formed, a cell with low stiffness may be realized and may bend, which may cause problems in the cell transfer process.
[0102] Hereinafter, the embodiments of the present invention will be described in detail so that a person having ordinary skill in the art to which the present invention belongs can easily carry out the embodiments. However, this is merely an example, and the scope of the present invention is not limited to the following contents.
[0103] [Production Preparation Example: Production of Coating Layer Forming Composition]
[0104] <Comparative Preparation Example 1: Preparation of a composition for forming a coating layer containing acetone as a solvent>
[0105] A polyvinylidene fluoride-hexafluoropropylene copolymer (Mw=350,000-500,000g / mol) having a hexafluoropropylene-derived monomer content of 15% by weight, which acts as a binder, was added to acetone (solvent) and dissolved at 60°C for 1 hour to prepare a polymer solution (solid content=25% by weight). Inorganic particles (Al2O3) having an average particle size (D50) of 0.1 μm were added to the polymer solution, and the inorganic particles were crushed and pulverized in a ball mill for more than 12 hours to prepare a composition for forming a coating layer in which polyvinylidene fluoride-hexafluoropropylene copolymer and Al2O3 were mixed in a weight ratio of 1:9.
[0106] <Comparative Preparation Example 2: Unlike Comparative Preparation Example 1, the content of hexafluoropropylene monomer is 8% by weight>
[0107] A composition for forming a coating layer was prepared in the same manner as in Comparative Preparation Example 1. However, a polyvinylidene fluoride-hexafluoropropylene copolymer in which the content of the hexafluoropropylene monomer was changed from 15% by weight to 8% by weight was used.
[0108] <Comparative Preparation Example 3: Unlike Comparative Preparation Example 1, the solid content in the polymer solution is different>
[0109] A composition for forming a coating layer was prepared in the same manner as in Comparative Preparation Example 1, except that the content of acetone was adjusted so that the solid content in the polymer solution was 20 wt %.
[0110] <Preparation Example 1: Production of a composition for forming a coating layer containing NMP as a solvent>
[0111] A composition for forming a coating layer was prepared in the same manner as in Comparative Preparation Example 1. However, N-methyl-2-pyrrolidone (NMP) was used instead of the acetone.
[0112] <Preparatory Example 2: Unlike Preparatory Example 1, the HFP monomer content is 8% by weight>
[0113] A composition for forming a coating layer was prepared in the same manner as in Preparation Example 1. However, a polyvinylidene fluoride-hexafluoropropylene copolymer in which the content of the hexafluoropropylene monomer was changed from 15% by weight to 8% by weight was used.
[0114] <Preparation Example 3: Unlike Preparation Example 1, the solvent content is different>
[0115] A composition for forming a coating layer was prepared in the same manner as in Preparation Example 1. However, the content of NMP (solvent) was adjusted to prepare a polymer solution with a solid content of 20 wt %.
[0116] <Comparative Preparation Example 4: Unlike Example Preparation Example 1, the content of HFP monomer is less than 8% by weight or more than 15% by weight>
[0117] An attempt was made to form a coating layer from a composition in the same manner as in Preparatory Example 1, using PVDF-HFP in which the HFP monomer content was changed to more than 15 wt% or less than 8 wt%. If the content was less than 8 wt%, the solubility of PVDF-HFP in the electrolyte was too good to be applied to batteries. If the content exceeded 15 wt%, the dispersibility was poor, making it difficult to apply to batteries.
[0118] [Production Example 1: Production of separator for secondary battery]
[0119] <Comparative Example 1: Production of separation membrane including coating layer according to Comparative Preparation Example 1>
[0120] The coating layer forming composition according to Comparative Preparation Example 1 was applied to both sides of a polyethylene porous substrate having a thickness of 9 μm and a porosity of 45% by a slot-die coating method, and then dried at 110° C. for 1 hour to form a coating layer having a thickness of 5 μm. At 110° C., slow evaporation of the solvent NMP was induced.
[0121] <Comparative Example 2: Production of separation membrane including coating layer according to Comparative Preparation Example 2>
[0122] A separator for a secondary battery was produced in the same manner as in Comparative Example 1. However, instead of the composition for forming a coating layer according to Comparative Preparation Example 1, the composition for forming a coating layer according to Comparative Preparation Example 2 was used.
[0123] <Comparative Example 3: Production of separation membrane including coating layer according to Comparative Preparation Example 3>
[0124] A separator for a secondary battery was produced in the same manner as in Comparative Example 1. However, instead of the composition for forming a coating layer according to Comparative Preparation Example 1, the composition for forming a coating layer according to Comparative Preparation Example 3 was used.
[0125] <Example 1: Production of separation membrane including coating layer according to Preparation Example 1>
[0126] A separator for a secondary battery was produced in the same manner as in Comparative Example 1. However, instead of the composition for forming a coating layer according to Comparative Preparation Example 1, the composition for forming a coating layer according to Working Preparation Example 1 was used.
[0127] <Example 2: Production of separation membrane including coating layer according to Preparation Example 2>
[0128] A separator for a secondary battery was produced in the same manner as in Example 1. However, instead of the composition for forming a coating layer according to Preparatory Example 1, the composition for forming a coating layer according to Preparatory Example 2 was used.
[0129] <Example 3: Production of separation membrane including coating layer according to Preparation Example 3>
[0130] A separator for a secondary battery was produced in the same manner as in Example 1. However, instead of the composition for forming a coating layer according to Preparatory Example 1, the composition for forming a coating layer according to Preparatory Example 3 was used.
[0131] [Experimental Example 1: Presence or absence of binder detachment in electrolyte]
[0132] Separator membrane specimens were manufactured by the method according to Comparative Example 1. However, three specimens were manufactured while changing the temperature and binder concentration. The three specimens (Comparative Examples 1-1 to 1-3) and the separator membrane specimen of Example 1 were immersed in an electrolyte for 24 hours, and then observed for the presence or absence of binder desorption, and the results are shown in Table 1 below. The electrolyte was a solution in which 1M LiPF6 was dissolved in a carbonate-based mixed solvent in which ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 1:1.
[0133] However, the binder concentration in Table 1 below is defined as the solid content in the polymer solution.
[0134] [Table 1]
[0135] Referring to Comparative Examples 1-1 to 1-3 in Table 1, it can be seen that when the solvent of the composition for forming a coating layer is acetone, the binder dissolves in the electrolyte and is released as the temperature increases. On the other hand, as in Example 1, when the solvent of the composition for forming a coating layer is N-methyl-2-pyrrolidone (NMP), it can be seen that the solubility in the electrolyte is low, and the swelling phenomenon of the binder is suppressed by the electrolyte. From these results, it can be inferred that when a coating layer is prepared using N-methyl-2-pyrrolidone, the inorganic particles can be well maintained under high temperature conditions, thereby improving the stability of the secondary battery.
[0136] [Experimental Example 2: Measurement of binder lamellar size depending on composition of coating layer forming composition]
[0137] FIG. 2 shows the change in lamellar thickness of the binder (PVDF-HFP) in the separator according to Examples 1 to 3 and Comparative Examples 1 to 3 when the solvent contained in the composition for forming a coating layer is changed. The lamellar thickness of the binder was analyzed by a small angle x-ray scattering (SAXS) device. After analysis through T-SAXS (Transmission-small angle x-ray scattering), model fitting was applied. Furthermore, a correlation curve was obtained by Fourier transformation, and the lamellar thickness was calculated by obtaining the crystallinity and the distance between the crystalline parts.
[0138] In FIG. 2, PVDF-HFP (8) is a case where a binder containing 8% by weight of HFP monomer is included, and the content of the solvent in the composition for forming a coating layer is about 23% by weight. PVDF-HFP (15) is a case where a binder containing 15% by weight of HFP monomer is included, and the content of the solvent in the composition for forming a coating layer is about 23% by weight. PVDF-HFP (15) * The case in which the composition for forming a coating layer contains a binder with an HFP monomer content of 15% by weight, and the content of the solvent in the composition for forming a coating layer is about 20% by weight.
[0139] Referring to FIG. 2, it can be seen that the average lamellar thickness of the binder in the coating layer contained in the separation membrane according to Examples 1 to 3 is 2.5 to 3.2 nm, and that the lamellar thickness of the binder in the coating layer contained in the separation membrane according to Comparative Examples 1 to 3 is less than 2.5 nm.
[0140] [Experimental Example 3: Solubility of binder in electrolyte depending on type of solvent when process temperature is changed during cell manufacturing]
[0141] FIG. 3 is a diagram showing the solubility of the binder in the electrolyte depending on the type of solvent when the process temperature is changed during cell production.
[0142] Referring to FIG. 3(a), it can be seen that by changing the solvent contained in the composition for forming a coating layer from acetone to N-methyl-2-pyrrolidone (NMP) at a temperature condition of 25° C., the separators according to Examples 1 and 3 have lower solubility of the binder in the electrolyte than the separators according to Comparative Examples 1 and 3.
[0143] 3(b), it can be seen that when the temperature condition of the process during cell manufacturing is increased from 25° C. to 55° C., the solubility of the binder contained in the coating layer of the separator according to Comparative Examples 1 to 3 in the electrolyte becomes too high. On the other hand, the binder contained in the coating layer of the separator according to Examples 1 and 3 can effectively prevent the solubility of the binder in the electrolyte from becoming too high compared to Comparative Examples 1 and 3.
[0144] [Experimental Example 4: Evaluation of wet adhesion of coating layer to porous substrate]
[0145] For the separator test pieces (20mm x 70mm) according to Comparative Examples 1 and 2 and Example 3, which were immersed in the electrolyte for 24 hours and then removed, a force was applied to the coating layer at a measurement speed of 200mm / min using a universal testing machine (UTM) to evaluate wet adhesion. Specifically, the electrolyte was composed of a solution in which 1M LiPF6 was dissolved in a carbonate-based mixed solvent in which ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 1:1.
[0146] Fig. 4a shows the results of wet adhesion evaluation of the coating layer to the porous substrate in the separation membrane of Comparative Example 1. Fig. 4b shows the results of wet adhesion evaluation of the coating layer to the porous substrate in the separation membrane of Example 3. Fig. 4c shows the results of wet adhesion evaluation of the coating layer to the porous substrate in the separation membrane of Comparative Example 2. Fig. 4d shows the results of wet adhesion evaluation of the coating layer to the porous substrate in the separation membrane of Comparative Example 1.
[0147] 4a to 4c, it can be seen that the separators of Examples 1 and 3 have higher wet adhesion strength of the coating layer to the porous substrate in an electrolyte injection environment than the separators of Comparative Examples 1 and 2.
[0148] [Experimental Example 5: Evaluation of air permeability of separator for secondary battery]
[0149] To measure the air permeability of the separators according to Comparative Example 1 and Example 1, an air permeability meter (manufacturer: Asahi Seiko, product name: EG01-55-1MR) was used to measure the time (sec) it took for 100cc of air to pass through the separator at a constant pressure (0.05MPa). Measurements were made at three points, one each on the left, center, and right sides of each separator, and the average was calculated. The results are shown in Table 2 below. The shorter the time it takes for 100cc of air to pass through the separator, the better the air permeability performance, which indirectly suggests that the rate characteristics of the battery are improved.
[0150] [Table 2]
[0151] Referring to Table 2, it can be seen that the use of NMP instead of acetone as a solvent for the composition for forming a coating layer results in excellent air permeability, which suggests that the rate characteristics of the secondary battery are improved.
[0152] [Manufacturing Example 2: Manufacturing of secondary batteries]
[0153] Secondary batteries were manufactured using the separators according to Comparative Example 1 and Examples 1 and 3. Specifically, the positive and negative electrodes were manufactured in the following manner.
[0154] (Production of positive electrodes)
[0155] In the case of the positive electrode, the positive electrode active material (LiNi 0.6 Co 0.2 Mn 0.2 O2), conductive material (FX35), and binder (PVDF) were added to a solvent (NMP) in a weight ratio of 95:2:3, and then stirred at 2,000 rpm for 30 minutes to prepare a cathode slurry. The cathode slurry was applied to a thin aluminum film with a thickness of 20 μm using a doctor blade, and then dried at 110°C (overnight) to prepare a rolled cathode.
[0156] (Production of negative electrodes)
[0157] Anode active material (graphite), conductive material (Super P) and binder (CMC:SBR = 1:1 (w / w)) were added to a solvent (water) in a weight ratio of 97.5:1.5:1.0 and stirred at 2,000 rpm for 30 minutes to prepare anode slurry. The anode slurry was applied to a copper foil with a thickness of 20 μm using a doctor blade and then dried at 110°C overnight to prepare a rolled anode.
[0158] (Secondary battery manufacturing)
[0159] The rolled positive electrode, the separator, and the rolled negative electrode were stacked in this order and then laminated to prepare an electrode assembly. The electrode assembly was inserted into a battery case, and an electrolyte was injected to prepare a secondary battery. The battery case into which the electrolyte was injected was stored at 55°C. The electrolyte was in the form of a solution in which 1M LiPF6 was dissolved in a carbonate-based mixed solvent in which ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 1:1.
[0160] [Experimental Example 6: SEM (Scanning Electron Microscope) Observation of Secondary Batteries]
[0161] Fig. 5 is a SEM (Scanning Electron Microscope) photograph of a secondary battery including the separator according to Comparative Example 1 and Example 1. Fig. 6 is a SEM (Scanning Electron Microscope) photograph of a secondary battery including the separator according to Comparative Example 1 and Example 1.
[0162] 5 and 6, it can be seen that the binder in the coating layer of the secondary battery including the separator according to Example 1 is not detached, whereas it can be seen that the binder in the coating layer of the secondary battery including the separator according to Comparative Example 1 is detached.
[0163] In particular, FIG. 6b shows that the binder (PVDF-HFP) in Example 1 does not peel off from the substrate, whereas in Comparative Example 1 (FIG. 6a), the binder peels off from the substrate.
[0164] [Experimental Example 7: Evaluation of capacity retention rate of secondary battery according to cycle]
[0165] For the secondary batteries including the separators according to Comparative Example 1 and Example 1, the capacity retention according to the cycle of three cells per set was evaluated using a charger / discharger manufactured by PNE Solution in the voltage range of 2.5 to 4.3 V.
[0166] FIG. 7 shows the capacity retention rate according to the number of cycles (3 cycles) of the secondary batteries including the separators according to Comparative Example 1 and Example 1.
[0167] 7, it can be seen that the secondary battery including the separator according to Example 1 maintains a higher capacity retention rate than Comparative Example 1 even with an increased number of cycles.
[0168] [Experimental Example 8: Cell stiffness comparison]
[0169] FIG. 8 shows the results of comparing the secondary battery cells including the separators according to Comparative Example 1 and Example 1.
[0170] Referring to FIG. 8, it can be seen that the cell of Comparative Example 1(a) has a problem of bending due to lack of wet adhesion, whereas the cell of Example 1(b) has a binder (PVDF-HFP) still present in the coating layer, realizing wet adhesion and maintaining good hardness.
[0171] Although the preferred embodiments of the present invention have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concept of the present invention defined in the following claims also fall within the scope of the present invention. [Explanation of symbols]
[0172] 10: Porous base material 20: Coating layer 100: Separation membrane for secondary batteries
Claims
1. A separator for a secondary battery, A porous substrate, and a coating layer disposed on at least one surface of the porous substrate; Including, The coating layer is Polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP), and inorganic particles Including, The polyvinylidene fluoride-hexafluoropropylene copolymer in the coating layer has a lamellar thickness of 2.5 to 3.2 nm.
2. 2. The separator for a secondary battery according to claim 1, wherein the porous substrate comprises at least one selected from the group consisting of polyolefin, polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfide, and polyethylene naphthalene.
3. 2. The separator for a secondary battery according to claim 1, wherein the inorganic particles are inorganic particles having a dielectric constant of 5 or more, inorganic particles having lithium ion transport ability, or a mixture thereof.
4. The inorganic particles are Al 2 O 3 , SiO 2 , ZrO 2 , AlO(OH), Al(OH) 3 , Mg(OH) 2 , BaSO 4 , TiO 2 , BaTiO 3 , Pb(Zr x Ti 1-x ) O 3 (PZT, where 0<x<1), Pb 1-x La x Zr 1-y Ti y O 3 (PLZT, where 0<x<1, 0<y<1, (1-x)Pb(Mg 1/3 Nb 2/3 ) O 3-x PbTiO 3 (PMN-PT, where 0<x<1), HfO 2 , SrTiO 3 , SnO 2 , CeO 2 , MgO, NiO, CaO, ZnO, SiC, lithium phosphate (Li 3 P.O. 4 ), lithium titanium phosphate (Li x Ti y (P.O. 4 ) 3 , 0<x<2, 0<y<3), lithium aluminum titanium phosphate (Li x A y Ti z (P.O. 4 ) 3 , 0<x<2, 0<y<1, 0<z<3), (LiAlTiP) x O y Lithium lanthanum titanate (Li x La y TiO 3 , 0<x<2, 0<y<3), lithium germanium thiophosphate (Li x Ge y P z S w , 0<x<4, 0<y<1, 0<z<1, 0<w<5), lithium nitride (Li x N y , 0<x<4, 0<y<2), SiS 2 Li-based glass x S y S z , 0<x<3, 0<y<2, 0<z<4), P 2 S 5 Li-based glass x P y S z 4. The separator for a secondary battery according to claim 3, wherein the y-axis is selected from the group consisting of 0<x<3, 0<y<3, 0<z<7) and mixtures of two or more thereof.
5. 2. The separator for secondary batteries according to claim 1, wherein the content of the hexafluoropropylene-derived monomer is 8 to 15% by weight based on the polyvinylidene fluoride-hexafluoropropylene copolymer.
6. 2. The separator for a secondary battery according to claim 1, wherein the polyvinylidene fluoride-hexafluoropropylene copolymer has a weight average molecular weight (Mw) of 300,000 to 600,000 g / mol.
7. 2. The separator for a secondary battery according to claim 1, wherein the separator for a secondary battery has an air permeability of 160 sec / 100 cc or less.
8. A method for producing a separator for a secondary battery, comprising: (S1) coating at least one surface of a porous substrate with a composition for forming a coating layer; and (S2) drying the composition for forming a coating layer to form a coating layer; Including, The coating layer forming composition is Polyvinylidene fluoride-hexafluoropropylene copolymer, Inorganic particles and solvent Including, The method for producing a separator for a secondary battery, wherein the solvent comprises a polar organic solvent having a boiling point of 120° C. or higher.
9. 9. The method of claim 8, wherein the composition for forming the coating layer in step (S2) is dried at 100 to 170° C. for 0.5 to 1.5 hours.
10. 9. The method of claim 8, wherein the polar organic solvent is selected from the group consisting of 4-dimethylaminopyridine, 1-pentanol, ethylene glycol, dimethylsulfoxide, dimethylformamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, and a mixture of two or more thereof.
11. The method of claim 8, wherein the content of the solvent is 20 to 40 wt % based on the total weight of the composition for forming the coating layer.
12. A separator for a secondary battery produced by the method according to any one of claims 8 to 11.
13. negative electrode, positive electrode, The separation membrane according to any one of claims 1 to 7, which is interposed between the negative electrode and the positive electrode; and electrolyte A secondary battery comprising:
14. A method for manufacturing a secondary battery, comprising: (S1) manufacturing an electrode assembly by sequentially stacking a positive electrode, the separator according to any one of claims 1 to 7, and a negative electrode; (S2) inserting the electrode assembly into a battery case and then injecting an electrolyte into the battery case; and (S3) storing the battery case containing the electrolyte at 55 to 65° C. A method for manufacturing a secondary battery comprising the steps of:
Citation Information
Patent Citations
Lithium secondary battery
JP2013089593A
Lithium secondary battery and method of manufacturing the same
JP2022516636A
Separator for electrochemical device with porous coating layer and Electrochemical device comprising the same
KR1020160032922A
Blade device for air conditioner
KR1020220102029A
Battery, separator, electrode, paint, battery pack, electronic device, electric vehicle, electricity-storage device, and power system
WO2015097953A1